Ways to prevent caries disease in children (Texas Journal of Medical Science, 2022)
At present, the increase in the number of nutrients, the increase in the content of organic substances with a maraca, the chemical composition of household appliances hasa serious impact on the microbiology of the oral cavity, which causes an increase in dental caries. At present, its prevention is much more important than the treatment of dental caries.